2016
DOI: 10.1021/acs.jpclett.6b00171
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Prediction and Characterization of Mo2C Monolayer as Anodes for Lithium-Ion and Sodium-Ion Batteries

Abstract: Identifying suitable electrodes materials with desirable electrochemical properties is urgently needed for the next generation of renewable energy technologies. Here we report an ideal candidate material, Mo2C monolayer, with not only required large capacity but also high stability and mobility by means of first-principles calculations. After ensuring its dynamical and thermal stabilities, various low energy Li and Na adsorption sites are identified, and the electric conductivity of the host material is also m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
261
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(281 citation statements)
references
References 58 publications
17
261
2
1
Order By: Relevance
“…To designate VO 2 monolayer as anode material for metal ion battery, we calculated the specic capacities using the following equation 54,58,60 C ¼ nN A e 3:6m MxVO 2 and Li and Na on Mo 2 N are 432 and 864 mA h g À1 . 14 The maximum Mg content is 1 resulting the theoretical capacity of 815 mA h g À1 , which is also higher than conventional electrode capacity.…”
Section: -59mentioning
confidence: 99%
“…To designate VO 2 monolayer as anode material for metal ion battery, we calculated the specic capacities using the following equation 54,58,60 C ¼ nN A e 3:6m MxVO 2 and Li and Na on Mo 2 N are 432 and 864 mA h g À1 . 14 The maximum Mg content is 1 resulting the theoretical capacity of 815 mA h g À1 , which is also higher than conventional electrode capacity.…”
Section: -59mentioning
confidence: 99%
“…However, graphene containing hybrids of TMDCs, TMOs, and MXenes are thoroughly discussed here. Computational studies predict that beyond graphene 2D materials can demonstrate advanced electrode characteristics [93][94][95][96][97][98][99][100][101][102][103], but in this review, we focus on experimental research and strategies that proved to be successful to improve performance of 2D materials in BLI batteries.…”
Section: Rechargeable Beyond Li-ion Batteriesmentioning
confidence: 99%
“…Most research aimed at understanding performance of MXene phases in BLI batteries is carried out by computational scientists [96][97][98][99][100][101][102], and experimental characterization, focused on Na-ion batteries, has emerged only in recent years. Ti 3 C 2 and Ti 2 C are two of the most studied MXene phases because of their well-established synthesis process and high electrochemical performance.…”
Section: Transition Metal Carbides and Carbonitridesmentioning
confidence: 99%
“…Benefiting from the novel exceptional properties and abundant species described above, TMCs have attracted considerable attention, and also have been widely investigated for various potential applications, especially as promising electrode materials for energy storage and conversion systems such as MIBs, SCs, RMABs, fuel cells, and water splitting. For instance, experimental results and theoretical calculations have revealed that TMCs can afford higher specific capacity/capacitance and longer lifetime than the carbon/graphite‐based materials for MIBs and SCs . As for those RMABs, fuel cells, and water splitting devices, which involve the electrocatalytic reactions (e.g., HER, OER and ORR), TMCs can exhibit desirable electrochemical performances.…”
Section: Introductionmentioning
confidence: 99%